Public accountability and institutional change in Latin America. Introduction to dossier - Adrián Gurza-Lavalle (Íconos)
After reviewing the main approaches about public accountability studies in Latin America, we open a dialogue with the authors who contributed to this dossier and provide some thoughts about the pending topics in the research agenda of public accountability in the region. We highlight the importance of an encompassing reading that would allow us to think in terms of democratic accountability regimes, beyond specific experiences of social, political or administrative control. We analyze the interdependence between these types of control through a typology based on coercion and par-ticipation in the interplays between the State and non-State actors. We then review the main challenges raised by the institutional changes that have occurred in Latin America since the democratic transitions. We argue that the scenario of public accountability and its different institutional mechanisms are more diverse and complex than what Guillermo O’Donnell’s theory of delegative democracy elaborated in the 1990s suggested. On the one hand, the functions of horizontal accountability were enforced in various countries, increasing the functional autonomy of (political) balance agencies, while the specialized (administrative) agencies acquired greater capacity. On the other hand, democratic in-novation expanded the incidence of social controls through the institutionalization of participative and non-electoral representative agencies. Finally, the diffusion of transparency policies has produced synergies with the opportunities created by other changes (social networks, among others).